Multimodal safety assessment of measles‐mumps‐rubella vaccination after pediatric liver transplantation. Issue 3 (1st October 2018) - Pittet, Laure F.; Verolet, Charlotte M.; McLin, Valérie A.; Wildhaber, Barbara E.; Rodriguez, Maria; Cherpillod, Pascal; Kaiser, Laurent; Siegrist, Claire‐Anne; Posfay‐Barbe, Klara M.
Abstract : Live‐attenuated vaccines are currently contraindicated in solid‐organ transplant recipients. However, the risk of vaccine‐preventable infections is lifelong, and can be particularly severe after transplantation. In this prospective interventional national cohort study, 44 pediatric liver transplant recipients with measles IgG antibodies <150 IU/L (below seroprotection threshold) received measles‐mumps‐rubella vaccine (MMR) at a median of 6.3 years posttransplantation (interquartile range, 4.0 to 10.9). A maximum of two additional doses were administered in nonresponders or when seroprotection was lost. Vaccine responses occurred in 98% (95% confidence interval [CI], 88‐100) of patients. Seroprotection at 1‐, 2‐, and 3‐year follow‐up reached 62% (95% CI, 45‐78), 86% (95% CI, 70‐95), and 89% (95% CI, 67‐99), respectively. All patients responded appropriately to the booster dose(s). Vaccinations were well tolerated and no serious adverse event attributable to vaccination was identified during the 8‐week follow‐up period (or later), using a multimodal approach including standardized telephone interviews, diarized side effect reporting, and monitoring of vaccinal virus shedding. We conclude that live attenuated MMR vaccine can be administered in liver transplant recipients fulfilling specific eligibility criteria (>1 year posttransplantation, low immunosuppression, lymphocyte count ≥0.75 G/L), inducing seroprotection in most subjects. (Clinicaltrials.gov number NCT01770119). Abstract : This prospective interventional study demonstrates the safety and immunogenicity of the live‐attenuated measles‐mumps‐rubella vaccine in immunocompromised children not seroprotected against measles after liver transplantation.